Return of the regulatory state: A stakeholder analysis of Australia's Digital Platforms Inquiry and online news policy. Issue 2 (15th March 2021) - Flew, Terry; Gillett, Rosalie; Martin, Fiona; Sunman, Lucy
Abstract: In this paper, we undertake a stakeholder analysis of the Australian Competition and Consumer Commission's Digital Platforms Inquiry to understand the nature and influence of different forms of public input. Our findings show that nation-state regulation of digital platforms is now very much on the policy agenda worldwide, with a focus upon the competition policy dimensions of platform regulation. The second key finding is that the regulatory activism of the ACCC have ensured that the Inquiry and its findings have had maximum public impact. Finally, we argue that the key dynamic shaping the Inquiry was the competing demands of the traditional news media publishers and digital platforms, and that civil society input was relatively limited and secondary to the final recommendations.